RNA viruses of Crithidia bombi, a parasite of bumblebees - Klocek, Donnamae; Grybchuk, Danyil; Macedo, Diego H; Galan, Arnau; Votýpka, Jan; Schmid-Hempel, Regula; Schmid-Hempel, Paul; Yurchenko, Vyacheslav; Kostygov, Alexei Yu (Journal of invertebrate pathology, 2023)
Leishbuviridae (Bunyavirales) are a diverse monophyletic group of negative-sense single-stranded RNA virus infecting parasitic flagellates of the family Trypanosomatidae. The presence of RNA viruses in trypanosomatids can influence the virulence of the latter. Here, we performed a screening for viruses in Crithidia bombi - a common parasite of important pollinators Bombus spp. (bumblebees) that negatively affects its host in stressful conditions. The majority (8/10) of C. bombi isolates collected in Europe and North America were positive for a virus that we named Crithidia bombi leishbuvirus 1 with high conservation of amino acid sequences between isolates. The results of our comparative phylogenetic analyses of the trypanosomatids and their viruses suggest that the high mobility of bumblebees and frequent coinfections by different strains of C. bombi determine an extensive viral exchange between the latter.
Keywords: Leishbuviridae; North America; Phylogeny; Crithidia; RNA-viry; RNA Viruses; fylogeneze; Animals; paraziti; Parasites; Viral transmission; Bees; Bombus; zvířata; včely; Severní Amerika